2017
DOI: 10.1190/tle36120987.1
|View full text |Cite
|
Sign up to set email alerts
|

Compressional- and shear-wave studies of distributed acoustic sensing acquired vertical seismic profile data

Abstract: Understanding the strengths and limitations of rapidly advancing distributed acoustic sensing (DAS) technology used for recording vertical seismic profile (VSP) data is achieved by comparing DAS and geophone data sets using both compressional-wave (P-wave) and shear-wave (S-wave) VSP data and their corresponding geophysical answer products. We validate the kinematics (time) and dynamics (amplitude) of DAS VSP data by examining the extracted slowness values, response-to-incident angles, corridor stacks, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 3 publications
0
17
0
3
Order By: Relevance
“…DAS technology enables acquisition of high-resolution seismological data at frequencies from the kHz to mHz for long distances (tens of km) and at very dense spatial samplings (down to 1 m) in contexts in which the use of conventional sensors is intricate and/or costly (Daley et al, 2016;Becker et al, 2017). DAS is incrementally being adopted in the field of applied geophysics and a variety of studies have demonstrated its suitability for a range of applications such as vertical seismic profiling (Daley et al, 2013;Mateeva et al, 2013;Wu et al, 2015;Wu et al, 2017), time-lapse monitoring of near-surface properties (Dou et al, 2017;Ajo-Franklin et al, 2019), earthquake detection (Lindsey et al, 2017;Ajo-Franklin et al, 2019;Li & Zhan, 2018), and hydrological monitoring (Becker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DAS technology enables acquisition of high-resolution seismological data at frequencies from the kHz to mHz for long distances (tens of km) and at very dense spatial samplings (down to 1 m) in contexts in which the use of conventional sensors is intricate and/or costly (Daley et al, 2016;Becker et al, 2017). DAS is incrementally being adopted in the field of applied geophysics and a variety of studies have demonstrated its suitability for a range of applications such as vertical seismic profiling (Daley et al, 2013;Mateeva et al, 2013;Wu et al, 2015;Wu et al, 2017), time-lapse monitoring of near-surface properties (Dou et al, 2017;Ajo-Franklin et al, 2019), earthquake detection (Lindsey et al, 2017;Ajo-Franklin et al, 2019;Li & Zhan, 2018), and hydrological monitoring (Becker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 9(b), the amplitude of the direct P-wave arrival changes with depth. The DAS measurement has directional sensitivity (Wu et al 2017); that is, the signal amplitude varies with the incident angle of the wave relative to the FO axis. The DAS amplitude for compressional waves decreases as the wave propagation direction becomes perpendicular to the FO, and the sensitivity to shear waves reaches its maximum at an incident angle of 45 degrees.…”
Section: I S T R I B U T E D a C O U S T I C S E N S I N G V E R T mentioning
confidence: 99%
“…; Humphries, Vidal and de Dios ; Wu et al . ) that had been published as of the end of 2017. In most of the existing field experiments, FOs were deployed via the behind casing or along tubing methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 33 used a shallow hydrogeologic pump test in a well with a fiber-optic cable to show that DAS has sensitivity to 9.4 × 10 −3 Hz (period = 1080 seconds) oscillations in strain induced by the variable confining pressure, presumably due to Poisson effects. This subject is complicated by the known directionality of DAS cables ( 34,35 ), which for the horizontal geometry of telecommunications dark fiber cables is theoretically insensitive to vertically-incident compressional motion (P-waves).…”
Section: Earthquake Seismology With a Dark Fiber Das Arraymentioning
confidence: 99%